1966
DOI: 10.1111/j.1151-2916.1966.tb13271.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Deformation of a Fireclay Refractory

Abstract: l a 1 T=1009'c U-718 P S I j I I / I I Rate process theory was applied in a study of the creep behavior of a fireclay refractory (firebrick) after different heat treatments. The analysis was based on the assumption that, in the absence of phase changes, equivalent deformation substructures are produced for a given strain at constant stress independent of temperature. An activation energy of about 170 kcal/mole was determined for the flow process in a heattreated firebrick, which corresponds closely to the valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1975
1975
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…It has been found that there are two types of tribofilms that are formed on the frictional body as a result of structural modification and interaction with the environment: (1) super-ductile and lubricating films [12]; and (2) tribo-ceramics with thermal barrier properties and increased hardness and strength [10,24,26,27,[30][31][32][33][34][35][36][37][38][39]. Tribofilms (SS) of the first type (SS-I) are observed as a result of structural activation marked by an increase in the density of atomic defects at the surface.…”
Section: Thermodynamics Of Tribofilmsmentioning
confidence: 99%
“…It has been found that there are two types of tribofilms that are formed on the frictional body as a result of structural modification and interaction with the environment: (1) super-ductile and lubricating films [12]; and (2) tribo-ceramics with thermal barrier properties and increased hardness and strength [10,24,26,27,[30][31][32][33][34][35][36][37][38][39]. Tribofilms (SS) of the first type (SS-I) are observed as a result of structural activation marked by an increase in the density of atomic defects at the surface.…”
Section: Thermodynamics Of Tribofilmsmentioning
confidence: 99%
“…Figure 4 presents TEM data on the microstructure of the surface of worn coated ball-nose end mill within a zone of the workpiece material buildup. [33][34][35][36][37] The 2.6 eV positive chemical shift of the XPS line Al 2s component can be interpreted as being related to the formation of Al 6 Si 2 O 13 mullite films. The first zone presents a tetragonal martensite structure of the adhered workpiece material ͑tool steel H13͒ that is related to EDX spectra ͑region 1͒.…”
Section: Resultsmentioning
confidence: 99%
“…That is why this coating can sustain even ultrahigh-speed [207][208][209][210][211][212][213][214][215][216], which is two times higher compared to the monolayered coating (table 2). XPS data indicates the formation of Al-Si-O bonds in Al 6 Si 2 O 13 mullite tribofilms [209][210][211][212]. The nonstoichiometric titanium tribo-oxide (7.3%) and rutile TiO 2 (5.5%, table 2) are also formed on the friction surface.…”
Section: Tribofilms (Secondary Structures)mentioning
confidence: 99%
“…This leads to formation of a nonstoichiometric titanium oxide films and rutile TiO 2 (table 2). XPS indicate formation of sapphire-like [207] triboceramics and nanofilms with a phase composition close to Al 6 Si 2 O 13 mullite [209][210][211][212][213][214]. A partial chemical transformation of aluminum in the TiAlCrSiYN monolayer coating has taken place: 28.6% of Al was retained in the complex nitride, 17.6% of aluminum oxidized with the formation of Al-Si-O oxide (mullite) and 8.8% of aluminum oxidized with the formation of trivalent Al 2 O 3 (sapphire, table 2).…”
Section: Tribofilms (Secondary Structures)mentioning
confidence: 99%
See 1 more Smart Citation